Phonon excitations in a single crystal Mg85Zn6Y9 with a synchronized long-period stacking ordered phase. (March 2018) - Hosokawa, Shinya; Kimura, Koji; Stellhorn, Jens Rüdiger; Yoshida, Koji; Hagihara, Koji; Izuno, Hitoshi; Yamasaki, Michiaki; Kawamura, Yoshihito; Mine, Yoji; Takashima, Kazuki; Uchiyama, Hiroshi; Tsutsui, Satoshi; et al.
Abstract: Inelastic X-ray scattering (IXS) experiments were carried out at room temperature at BL35XU of the SPring-8 on a single crystal Mg85 Zn6 Y9 alloy with a synchronized long-period stacking ordered (LPSO) phase of purely 18R type. The IXS measurements were carried out in both the longitudinal and transverse directions along the Γ -K and Γ -M (momentum vector q ⊥ lattice axis c ), and Γ -A ( q ∥ c ) directions for the energy transfers ω below 40 meV. Peaks arising from longitudinal and transverse acoustic (LA and TA) modes were clearly observed in the IXS spectra. The dispersion relations of the LA and TA modes in the Mg85 Zn6 Y9 LPSO alloy are mostly similar to those of previous INS data on single crystal pure Mg. New impurity-derived dispersion-less excitation modes are observed along all of the crystal directions at about 5, 10, and 17 meV. Partial vibrational density of states (vDOS) was obtained using an a b i n i t i o molecular dynamics simulation, and it was found that the ∼ 10 meV peak mainly originates from the phonon excitations inside the L12 -type Zn6 Y8 clusters and the ∼ 17 meV peak from those between the cluster and the host Mg atoms, and a small shoulder at 5 meV consists of motions of all the elements. These findings clarify that the dispersion-less modes mainly correspond to localized stretching and twisting modes around the impurity clusters in the LPSO alloys. Graphical abstract: Image 1